PERAN KEPALA SEKOLAH SEBAGAI MOTIVASI DALAM PENINGKATAN KINERJA GURU DI SMP MUHAMMADIYAH 05 MEDAN - Amalia Br Kaban; Nurul Hidayah Tambusai; Viani Alya Masyshra (Cemara Education and Science, 2024)
The implementation of tasks in educational units is considered crucial to achieve the set targets. Tasks are assigned to systems deemed capable of executing them effectively. This study aims to analyze the role of the principal as a motivational factor in improving teacher performance at SMP Muhammadiyah 05 Medan. The approach used in this research is qualitative with a descriptive method. Data collection techniques include interviews with key informants, observations, reference tracing, and documentation. Data analysis is conducted through data reduction, data display, and conclusion drawing, while ensuring data validity standards are maintained. The results of this study indicate that the distribution of tasks in educational units must align with the individual expertise of each professional to ensure tasks are completed optimally and not neglected